Wildfowl research and conservation in Europe in 1961 - Gudmundsson, Finnur; Grenquist, Pekka; Curry-Lindhal, Kai; Paludan, Knud; Holgersen, Holger; Kumari, Erik; Bruijns, M F Mrzer; Eygenraam, J A; Lippens, L; Bateman, J V; Roux, Francis; Schifferli, A; et al. (Wildfowl, 1962)
National activity and international co-operation in problems of research and conservation have quickened in recent years. The purpose of the series of reports presented here is to show what has been happening in various parts of Europe. From an insular point of view this may be useful in putting the efforts of the Wildfowl Trust and other British organisations into the European setting from which they cannot properly be separated. From a wider viewpoint it may be helpful to have available a summary showing what research work is actively in progress and, in the field of conservation, to be able to see how far the problems of different countries are common ones.